PENGGUNAAN GADGET ANDROID TERHADAP MORAL SISWA KELAS II SMP N 1 MAPAT TUNGGUL KABUPATEN PASAMAN - Nuraiman, Nuraiman; Deni, Leni Puspa (Jurnal Manajemen Pendidikan, 2021)
This research in the background by many of the moral declines that occurred in grade II students of SMP N 1 Mapat Tunggul in Pasaman Regency resulted from the use of Android Gadgets. This research aims to describe how android gadgets are used among grade II students of SMP N 1 Mapat Tunggul. To identify how the impact of the use of android gadgets on the morale of grade II students of SMP N 1 Mapat Tunggul and to find out how the efforts of schools, teachers and parents in limiting the use of android gadgets among grade II students of SMP N 1 Mapat Tunggul. The results showed that the use of android gadget technology among class II students of SMP N 1 Mapat Tunggul was very much, almost all students were active on average in using android gadgets which made students forget the time and place in their use. Only a small part of the students of SMP N 1 Mapat Tunggul who do not have an android gadget, namely students from low economic circles. As for efforts to overcome the negative impact of using Android Gadgets, the first is the school by making strict regulations. The second effort that can be done by the teacher is to instill religious values ​​in children and monitor every child's behavior. The three efforts that can be done by parents are to give more attention to children and monitor every child's behavior and provide limits on when children are allowed to play android gadgets and when they are not.